Analisa User Experience pada TFME Interactive Learning Media Menggunakan User Experience Questionnaire - Sandi Prasetyaningsih; Widya Putri Ramadhani (JURNAL INTEGRASI, 2021)
One of the cutting-edge technologies implementations can be seen on interactive multimedia that usually use in learning systems. School and informal education institutions start to use this system as their main media to deliver courses. For instance, Teaching Factory Manufacturing of Electronics (TFME) in Politeknik Negeri Batam. This study aims to generate interactive media that run on websites and to observe the experience value while using interactive media of TFME. ADDIE is utilized as a design method of system. ADDIE stands for analysis, design, development, implementation, and evaluation. Furthermore, during the research, qualitative method is used to analyze user experience questionnaire (UEQ) which has six scales, namely novelty, perspicuity, dependability, efficiency, attractiveness, and stimulation. The result of study shows that product can be employed as interactive multimedia for students well as UEQ’s scale has average > 0.8. It can be detailed in novelty (1.03), perspicuity (1.09), dependability (1.18), efficiency (1.15), attractiveness (1.23), and stimulation (1.20).